The role of institutional approach management processes in the formation of environmentally safe and highly efficient agricultural land use - Dorosh, O.; Dorosh, Y.; Zastulka, I.-O. (Land Management, Cadastre and Land Monitoring, 2022)
The article analyzes the management processes based on the institutional approach to agricultural land use management and finds that so far there have been no changes in priorities in these processes, due to the crisis situation in such land use. It is substantiated that institutional support for the development of highly efficient and environmentally friendly agricultural land use is achieved through management processes aimed at the formation, full functionality and legitimacy of such institutions as: Institute of Land Management, Institute of State Land Cadastre, Institute of Land Valuation, Institute of Land Use Monitoring that complement and characterize each other. In this regard, the institutional framework for reforming land relations in terms of a deeper understanding of management phenomena, processes to ensure the implementation of social, economic and environmental values in society and ensure systemic development of land use should be changed. As the main tools for achieving highly efficient and environmentally friendly agricultural land use, public authorities should first of all produce universally binding socially necessary clearly defined requirements, norms, rules and regulations and monitor their strict implementation by economic entities. It is proved that the chosen approach reflects the needs of society in this area.Key words: state regulation, land use institutions, land management regulations, highly efficient agricultural land use, environmentally friendly agricultural land use.